2022
DOI: 10.5334/ijic.6011
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Care in Complex and Fragmented Service Systems: Experiences of Staff in Flexible Assertive Community Treatment Teams

Abstract: Introduction: To provide more integrated care, several countries have implemented the Flexible Assertive Community Treatment (FACT) model. However, this model does not guarantee full integration, especially in complex and fragmented service systems like in Norway. Hence, we investigated which barriers that might reduce the potential for integrated care in the Norwegian system, as described by staff in FACT teams, and how they adjust their way of working to increase the opportunities for integratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…Delegation of tasks to primary care appeared to be a modification that maintained outreach intensity to some extent and improved crisis management. However, this means that the FACT teams must collaborate with other services and co-ordinate care they do not provide themselves, which might be challenging ( 30 ). Therefore, a high degree of delegation of tasks to other services can make the teams depart further from the FACT model, which specifies that other services should be used as little as possible to ensure a good overview and co-ordination ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Delegation of tasks to primary care appeared to be a modification that maintained outreach intensity to some extent and improved crisis management. However, this means that the FACT teams must collaborate with other services and co-ordinate care they do not provide themselves, which might be challenging ( 30 ). Therefore, a high degree of delegation of tasks to other services can make the teams depart further from the FACT model, which specifies that other services should be used as little as possible to ensure a good overview and co-ordination ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a high degree of delegation of tasks to other services can make the teams depart further from the FACT model, which specifies that other services should be used as little as possible to ensure a good overview and co-ordination ( 17 ). Neither urban nor rural Norwegian FACT teams provide all services themselves and co-ordination and collaboration are needed ( 30 ). This appears to be reinforced by the rural context, where even more services are provided by others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The FACT model fidelity of this team was assessed as strong. 6 For more information on the context of the FACT teams and the leading project, please refer to Brekke et al (2021) and Trane et al (2021Trane et al ( , 2022aTrane et al ( , 2022b.…”
Section: Contextmentioning
confidence: 99%
“…Two studies by Trane et al [7,10] examined the implementation of the FACT model in Norway. One of the studies looked at barriers for integrated care in a fragmented service system such as the Norwegian system, which showed that different digital systems, including EHR systems, represented a major barrier to integrated care [10]. This was described as a factor that could lead to errors in medication.…”
Section: Introductionmentioning
confidence: 99%